2008
DOI: 10.4049/jimmunol.180.2.1249
|View full text |Cite
|
Sign up to set email alerts
|

MHC Class II Derived Recombinant T Cell Receptor Ligands Protect DBA/1LacJ Mice from Collagen-Induced Arthritis

Abstract: We previously demonstrated the therapeutic effects of MHC class II derived recombinant T cell receptor ligands (RTL), single-chain two domain complexes of the α1 and β1 domains of MHC class II molecules genetically linked with an immunodominant peptide, in experimental autoimmune encephalomyelitis. In the current study, we produced a monomeric murine I-Aq-derived RTL construct covalently linked with bovine collagen type II peptide (bCII257–270) suitable for use in DBA/1LacJ mice that develop collagen-induced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…This approach has shown promising results for multiple sclerosis treatment, showing solid results in phase I clinical study [136] and also has demonstrated a potential use for other autoimmune diseases [137,138]. Briefly, the goal of this strategy is the same than the one targeted for the above mentioned HLA-blocker peptides: to modulate the immune response; although for each one the target would be different.…”
Section: Novel Treatments In CDmentioning
confidence: 97%
“…This approach has shown promising results for multiple sclerosis treatment, showing solid results in phase I clinical study [136] and also has demonstrated a potential use for other autoimmune diseases [137,138]. Briefly, the goal of this strategy is the same than the one targeted for the above mentioned HLA-blocker peptides: to modulate the immune response; although for each one the target would be different.…”
Section: Novel Treatments In CDmentioning
confidence: 97%
“…Partial MHC class II constructs were shown previously to prevent and/or reverse clinical signs of EAE, collagen-induced arthritis and experimental autoimmune uveitis, through reducing the number and frequency of activated cells in the affected tissues, downregulation of endothelial cell adhesion molecules and reduction of CNS chemokines/receptors (Adamus et al, 2012; Adamus et al, 2006; Huan et al, 2008; Sinha et al, 2010; Sinha et al, 2007). Based on these findings, a pMHC construct (RTL551, mouse I-A b α1β1 domains linked to mouse MOG-35-55 peptide) was used to treat experimental stroke in C57BL/6 mice.…”
Section: Treating Ischemic Stroke With Partial Mhc Class II Constructsmentioning
confidence: 99%
“…Unlike four-domain MHC II molecules that can induce T cell activation and apoptosis (12), RTL are partial agonists that deviate autoreactive T cells to become non-pathogenic (13,14). We previously demonstrated that RTL could prevent and/or reverse clinical signs of experimental autoimmune encephalomyelitis (EAE) (15-17), collagen-induced arthritis (18) and experimental autoimmune uveitis (19). Recent studies with RTL551 (I-A b molecule covalently tethered to mouse myelin oligodendrocyte glycoprotein - mMOG-35−55 peptide), showed dramatic reversal of MOG-35−55-induced EAE, reduction of pathogenic CNS cells, down-regulation of endothelial cell adhesion molecules (ICAM and VCAM) and broad reduction of CNS chemokines/receptors (20).…”
Section: Introductionmentioning
confidence: 99%